Livy's Cossus and Augustus, Tacitus' Germanicus and Tiberius: a Historiographical Allusion - Shannon, Kelly (Histos, 2011)
In his description of the German chieftain Inguiomerus (Ann. 2.21.1), Tacitus uses phrasing (tota volitantem acie) that recalls Livy’s description of the king Lars Tolumnius in his account of Rome’s struggles against Veii (4.19.2–3). Both passages use similar religious language to establish a sharp dichotomy between the religious Romans and their irreligious opponents, and the reference also illuminates the nature of political honors and power under Tiberius: by casting Inguiomerus as Tolumnius, Tacitus implicitly draws a comparison between Germanicus and Cossus, a figure best known for winning the spolia opima, and this recalls the controversial question of Cossus’ political office at the time he dedicated these spolia, and Crassus’ failure to dedicate spolia opima in the time of Augustus, an issue with special relevance for Tacitus’ Germanicus, who must downplay his military successes to avoid angering Tiberius. This allusion has important implications not only for Tacitus’ portrayal of the emperor but also for the question of intertextuality in historiography more generally.